Along-strike variations of the partitioning of convergence across the Haiyuan fault system detected by InSAR - Daout, S. (2020)
Oblique convergence across Tibet leads to slip partitioning with the coexistence of strike-slip, normal and thrust motion on major fault systems. A key point is to understand and model how faults interact and accumulate strain at depth. Here, we extract ground deformation across the Haiyuan Fault restraining bend, at the northeastern boundary of the Tibetan plateau, from Envisat radar data spanning the 2001-2011 period. We show that the complexity of the surface displacement field can be explained by the partitioning of a uniform deep-seated convergence. Mountains and sand dunes in the study area make the radar data processing challenging and require the latest developments in processing procedures for Synthetic Aperture Radar interferometry. The processing strategy is based on a small baseline approach. Before unwrapping, we correct for atmospheric phase delays from global atmospheric models and digital elevation model errors. A series of filtering steps is applied to improve the signal-to-noise ratio across high ranges of the Tibetan plateau and the phase unwrapping capability across the fault, required for reliable estimate of fault movement. We then jointly invert our InSAR time-series together with published GPS displacements to test a proposed long-term slip-partitioning model between the Haiyuan and Gulang left-lateral Faults and the Qilian Shan thrusts. We explore the geometry of the fault system at depth and associated slip rates using a Bayesian approach and test the consistency of present-day geodetic surface displacements with a longterm tectonic model. We determine a uniform convergence rate of 10 [8.6-11.5]mm yr-1 with an N89 [81-97]°E across the whole fault system, with a variable partitioning west and east of a major extensional fault-jog (the Tianzhu pull-apart basin). Our 2-D model of two profiles perpendicular to the fault system gives a quantitative understanding of how crustal deformation is accommodated by the various branches of this thrust/strike-slip fault system and demonstrates how the geometry of the Haiyuan fault system controls the partitioning of the deep secular motion.